2016
DOI: 10.1177/1359105315580460
|View full text |Cite
|
Sign up to set email alerts
|

Unresolved trauma in fibromyalgia: A cross-sectional study

Abstract: This study examined the prevalence of unresolved attachment-related trauma and its association with physical and psychological health status in 34 patients with fibromyalgia. Unresolved trauma was assessed with the Adult Attachment Interview. In addition, participants completed self-report measures of childhood trauma, fibromyalgia-related health status and depression. Of the sample, 50 per cent was classified as unresolved on the Adult Attachment Interview. Neither interview-based ratings of unresolved trauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
(24 reference statements)
1
10
1
1
Order By: Relevance
“…We think that this may be due to our small sample size; in fact, this PTLE has only been reported by two studies and appears with a frequency of 18% in a sample of 600 people, and only one case is included in another sample of 34 patients . Additionally, the PTLEs found are attributed to psychosocial rather than medical factors, which is in line with the findings of most other studies . On the other hand, at the level of analysis of specific PTLEs, none of the published research reported percentages similar to those obtained in our study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We think that this may be due to our small sample size; in fact, this PTLE has only been reported by two studies and appears with a frequency of 18% in a sample of 600 people, and only one case is included in another sample of 34 patients . Additionally, the PTLEs found are attributed to psychosocial rather than medical factors, which is in line with the findings of most other studies . On the other hand, at the level of analysis of specific PTLEs, none of the published research reported percentages similar to those obtained in our study.…”
Section: Discussionsupporting
confidence: 83%
“…Several studies have utilized qualitative methodologies, such as in‐depth interviews and life histories, leading some researchers to propose a distinction between traumatic and non‐traumatic fibromyalgia . Other studies have used psychometric instruments to find PTLEs; a number found a higher prevalence of psychosocial events, while others found a higher prevalence of physical events (eg surgery, accidents, childbirth, and pregnancy) . However, few studies have organized PTLEs into more general categories.…”
Section: Introductionmentioning
confidence: 99%
“…These authors identified different clusters of FM, with a cluster of patients reporting most pain and disability having the highest scores on CA. Yet, other studies have also typically failed to find a relationship between CA and pain severity in FM (Aaron et al., ; Waller et al., ). It is possible that other measures, for example, disability, are more appropriate than pain intensity to demonstrate an impact of CAs on the clinical outcome of FMS‐patients.…”
Section: Discussionmentioning
confidence: 97%
“…Alexithymia and FMS share several factors, including a close link with trauma and dissociation as a defense mechanism. In fact, several authors have confirmed the role of traumatic experiences on the onset and the presence of fibromyalgia as well as in individuals with alexithymia (7,8). Individuals with alexithymia seem to confer much more weight to the physical sensation of arousal instead of interpreting it, which remains suspended somehow.…”
Section: Introductionmentioning
confidence: 95%